Cardiopulmonary Responses to Ramadan Fasting in Hypertensive Patients: A Multigroup Comparative Study - Sukarmin; Edy Soesanto; Yulisetyaningrum; Ratna Aryani (The Indonesian Institute of Science and Technology Research, 2025)
Hypertension remains a major global health challenge, prompting exploration of culturally relevant interventions such as Ramadan fasting. This study evaluated the effects of varying Ramadan fasting intensities on cardiovascular parameters among hypertensive patients. An observational design was applied to 159 participants in a community-based management program in Pati Regency, Indonesia, categorized into non-fasting, partial fasting, and full fasting groups. Systolic blood pressure (SBP) slightly increased in the non-fasting group (164.38 ± 19.12 to 166.04 ± 20.29 mmHg; p = .019), whereas both partial and full fasting groups showed significant SBP reductions (partial: 169.76 ± 16.96 to 163.86 ± 14.30 mmHg; p < .001; full: 171.79 ± 12.78 to 161.07 ± 13.15 mmHg; p < .001). A similar pattern was observed in diastolic blood pressure (DBP), with no significant change in the non-fasting group (p = .182), but significant decreases in the partial (99.28 ± 5.36 to 93.25 ± 6.27 mmHg; p < .001) and full fasting groups (102.86 ± 5.99 to 95.00 ± 6.38 mmHg; p < .001). Only the full fasting group showed a significant reduction in heart rate (97.54 ± 5.81 to 84.25 ± 4.54 bpm; p < .001), while oxygen saturation remained stable across all groups. These findings suggest that full Ramadan fasting provides substantial cardiovascular benefits, supporting its potential as a culturally grounded, non-pharmacological approach hypertension management.